PERAN KELUARGA DALAM MENGATASI PERKAWINAN USIA MUDA DI DUSUN SP 1 MERBANG KECAMATAN BELITANG HILIR - Resi, Regina (UNIVERSITAS TANJUNGPURA, 2017)
This research entitled â€œFamily Role in Preventing Child Marrriage at SP 1 Merbang Village in Belitang Hilir Districtâ€. Main problem in this research is: how is parentsâ€™ role in performing family affection function, socialization function, and social monitoring function in preventing child marriage at SP 1 Merbang Village in Belitang Hilir District. This research aims to find out the family role in preventing child marriage at SP 1 Merbang Village in Belitang Hilir District. Method used was qualitative with descriptive analysis. Data collecting tools used were observation guide, interview guide, and document. The results were. (1) parents role in performing family affection role was by giving attention and affection to the children, and giving supporting advice toward the problems. (2) family socialization functioned to apply values and norms by teaching politeness, good deeds, and never hit the children. (3) family social monitoring functioned to monitor childrenâ€™s daily social intercourse, friends of the same age, mobile phone usage, and restrict the night activity.Keywords: Family Role, Marriage of Young Age.